Traditional Knowledge on Uncultivated Green Leafy Vegetables (UCGLVS) Used in Nalgonda District of Telangana - Soujanya, Kanneboina; Kumari, B. Anila; Jyothsna, E.; Kiran, V. Kavitha (International Journal of Bio-resource and Stress Management, 2021)
The present study data on traditional knowledge and identification of uncultivated edible greens (UCGLVs) used by the people of Nalgonda district, Telangana state, India was carried out through a structured questionnaire. The data was collected from three selected villages and 90 farm women were interviewed. The compiled information shows that 22 wild edible plant species belong to 19 genera and 14 families were identified from Nalgonda district, Telangana state. Among the identified plants, most of the plants species belongs to Amaranthaceae family. People are still consuming these wild greens during their availability due to several reasons like taste, nutritious, healthy, pesticide free, free of cost and easy availability. These UCGLVs were used in traditional medicine to treat many diseases like piles, constipation, anaemia, injuries, kidney problems, back pain problems, bleeding nose and some allergies. Even though there are many health, nutritional and economical benefits with the consumption of UCGLVs, some people are not using these uncultivated green leafy vegetables presently. Reasons like increased food production, markets, availability of food, urbanization, modernization, lack of knowledge on uncultivated food, unacceptability of taste, plant infestation during rainy season and some beliefs of the people was responsible for the underutilization of uncommon green leafy vegetables. Creating awareness on uncultivated greens, their health benefits and the provision of nutritional data helps to increase dietary diversity, improves health and decrease the burden of micronutrient deficiencies.